The public awareness of science and technology Malaysia 2008 - Mohd. Asraf, Ratnawati; Sheikh Ahmad, Ismail; Ssekamanya, Siraje Abdallah; Abu Kassim, Noor Lide; Tunku Ahmad, Tunku Badariah; Abd Rahman, Nik Suryani (Malaysian Science and Technology Information Centre (MASTIC), 2010)
Malaysian Science and Technology Information Centre(MASTIC) set out to assess the public’s awareness and understanding of, interest in, and attitude towards S&T. The first study on The Public’s Awareness of S&T was conducted in 1994, and subsequently, in 1996, 1998, 2000, 2002 and 2004. This is the seventh survey in a series of surveys on The Public’s awareness of S&T, and was aimed at assessing the public’s awareness and understanding of, interest in, and attitudes towards S&T, and their corresponding factors. It is important to ask these questions as they indicate the public’s interest in and attitude towards, and how interested they are in S&T, which affect their later commitment to S&T. Knowing the answers to these questions would enable us to propose and then implement appropriate strategies that could increase the public’s interest in and understanding of S&T, so that they would be more inclined to contribute to the growth of S&T in the country.